The Effect of Reading Comics via Webtoons on Senior High School Students’ Reading Comprehension: A Case Study - Nur Evi Hamiru; Alberth Alberth; La Ode Nggawu (Journal of Language Education and Educational Technology (JLEET), 2023)
This study aimed to investigate the impact of group (Comic Webtoon class and Conventional class) and gender (male and female) on reading comprehension among Class X IPA students at SMAN 2 Baubau. The sample comprised 72 students from Class X IPA 1 and Class X IPA 2, selected via purposive sampling. Data on reading comprehension were gathered using a 40-item multiple-choice test. Analysis employed descriptive statistics and two-way ANOVA. Results showed no significant main effect of groups on reading comprehension (p = 0.367 > 0.05), while a significant main effect of gender was observed (p = 0.00 < 0.05). Furthermore, an interaction effect of gender and groups on reading comprehension was found (p = 0.02 < 0.05). These findings underscore the need for educators to tailor reading materials and instructional methods based on gender differences and emphasize the importance of selecting appropriate reading media to enhance students' comprehension of diverse texts.